2013
DOI: 10.3168/jds.2012-5922
|View full text |Cite
|
Sign up to set email alerts
|

Metritis in dairy cows: Risk factors and reproductive performance

Abstract: The objectives of this study were to assess the risk factors for metritis, its effects on milk yield and on reproductive performance, and the efficacy of ceftiofur therapy in Holstein dairy cows. Cows (n=303) from a commercial dairy herd in Argentina were studied. Cows were scored for body condition, and blood samples were collected on d -14, 7, 21, 31, 41, and 50 relative to parturition. Cows having a watery, purulent, or brown, and fetid vaginal discharge (VD) and rectal temperature ≤ 39.2°C were diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
138
8
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(178 citation statements)
references
References 43 publications
22
138
8
10
Order By: Relevance
“…Metritis is caused by pathogens identified as facultative pathogenic bacteria (12,22). Many of them commonly exist, however, in cows 10-14 days after delivery (23) and the immune status of a cow's uterus determines the onset of metritis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Metritis is caused by pathogens identified as facultative pathogenic bacteria (12,22). Many of them commonly exist, however, in cows 10-14 days after delivery (23) and the immune status of a cow's uterus determines the onset of metritis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the risk of culling are variable (reviewed by Beaudeau et al, 2000), with some studies finding an "unfavourable association" between metritis and culling, but others not (see also Bonneville-Hebert et al, 2011). Similarly, Giuliodori et al (2013) found a lower risk of pregnancy and Ribeiro et al (2013) a lower pregnancy rate per artificial insemination for cows with metritis, while metritis did not affect firstservice conception rate or 150 days' pregnancy rate in the study of Benzaquen et al (2007).…”
Section: Impact Of Reproductive Disorders (Dystocia and Metritis)mentioning
confidence: 88%
“…More severe stages of the disease are associated with systemic signs of ill health such as fever (Giuliodori et al, 2013). According to a review by Galvao (2012), the average incidence is about 20 %, but reported incidences vary substantially, from as low as 2-4 % (Gröhn et al, 1990;Fourichon et al, 2001;Koeck et al, 2010;Yin et al, 2014), to 8-11 % (Garcia et al, 2005;Hossein-Zadeh and Ardalan, 2011;Koeck et al, 2012) and even 39 % (Martinez et al, 2012).…”
Section: Impact Of Reproductive Disorders (Dystocia and Metritis)mentioning
confidence: 99%
“…Viendo a la endometritis subclínica desde una perspectiva práctica, la estrategia para disminuir su prevalencia consiste en disminuir la incidencia de patologías del puerperio y, aunque la etiología de estas patologías es multifactorial, una constante que determina en gran medida la evolución de las vacas durante el puerperio son los cambios metabólicos ocasionados por la pérdida de condición corporal posparto. Las vacas más susceptibles a las patologías uterinas posparto son las que pierden mayor condición corporal después del parto (9,20,21) . Cabe señalar que la endometritis subclínica no es una patología exclusiva del ganado lechero, sino también se ha diagnosticado en bovinos en sistemas de producción de carne (22,23) .…”
Section: Discussionunclassified